2005
DOI: 10.1007/s10067-005-0095-z
|View full text |Cite
|
Sign up to set email alerts
|

Sporothrix schenckii infection presented as monoarthritis: report of two cases and review of the literature

Abstract: Septic arthritis demands early diagnosis and correct treatment if the function of the joint is to be restored. Sometimes, as in fungal infection, signs and symptoms may be mild and the diagnosis delayed. Nevertheless, the outcome of fungal arthritis is severe and usually causes joint disability. The authors report two patients with chronic monoarthritis due to Sporothrix schenckii infection diagnosed by synovial fluid cultures. Their clinical presentation, laboratory and image findings, and their treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 10 publications
0
27
0
2
Order By: Relevance
“…In immunocompetent patients, monoarthritis is more frequent than multiple articular involvement. The rarity of musculoskeletal disease in addition to the scarcity of fungal elements in synovial fluid culture and synovial histopathology often delays the diagnosis (11). According to Howell and Toohey, there were only 51 cases of sporothrical arthritis reported in the English literature up to 1998 (102).…”
Section: Pathogenesis and Clinical Forms Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In immunocompetent patients, monoarthritis is more frequent than multiple articular involvement. The rarity of musculoskeletal disease in addition to the scarcity of fungal elements in synovial fluid culture and synovial histopathology often delays the diagnosis (11). According to Howell and Toohey, there were only 51 cases of sporothrical arthritis reported in the English literature up to 1998 (102).…”
Section: Pathogenesis and Clinical Forms Human Diseasementioning
confidence: 99%
“…Nocardiosis (caused mainly by Nocardia brasiliensis), chromoblastomycosis, cryptococcosis, blastomycosis, and cat scratch disease also can be differential diagnoses. Sporotrichosis can also mimic cutaneous bacterial infections, sarcoidosis, lupus vulgaris, tuberculosis, and scrofuloderma, among others (11,188,268). These conditions should be differentiated by history, areas of endemicity, and lab tests.…”
Section: Pathogenesis and Clinical Forms Human Diseasementioning
confidence: 99%
“…Pulmonary, osteoarticular, meningeal, and disseminated sporotrichosis infections are associated with infection of sporothrixschenckii (2)(3)(4)(5)(6). The symptoms of these infections are similar to those of rheumatoid arthritis, as well as those of other connective tissue diseases and angiitis syndromes (7)(8)(9). Only a few studies have reported cases of sporotrichal arthritis patients, in whom disseminated sporotrichosis was induced by immunosuppressive therapy and biological agents (10,11).…”
Section: Introductionmentioning
confidence: 76%
“…Patients with disseminated-type sporotrichosis, who have smoking and/or alcohol drinking habits, suffer from diabetes mellitus, chronic obstructive pulmonary disease, and/or acquired immunodeficiency syndrome, or have immunosuppressive therapy are considered to fall into a high risk group (2-6, 10, 11). The comparison between sporotrichal arthritis and rheumatoid arthritis is shown in Table 1 (7,8,18). Good similarities are observed in distribution of arthritis, images, and pathology between these diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Диссе-минированные формы возникают преимущественно у им-мунокомпрометированных больных и протекают с пора-жением любых органов и систем, включая опорно-двига-тельный аппарат, легкие и головной мозг. В отличие от других микозов для споротрихоза характерен как моно-, так и олиго-/полиартрит с преимущественным поражени-ем коленных (64%), лучезапястных (50%), локтевых (24%) и голеностопных (20%) суставов [30]. При этом рентгено-логические проявления варьируют от околосуставного ос-теопороза до выраженных изменений по типу «симптома пробойника».…”
Section: споротрихозunclassified